Four new genera of European Pteromalidae (Hymenoptera), with some taxonomic changes (Bollettino di zoologia agraria e bachicoltura, 2024)
Four new genera, with their respective type species (also ali new) are described: Anorbanus barbieri from Algeria, Sedma dispar from France (incl. Corsica) and Greece, Monoksa dorsiplana from Israel, and Obalana brevigaster from Yugoslavia. New taxonomic changes are being proposed concerning 26 genera: 21 generic names and 17 species names are either placed in synonymy or, in cases of some genera, the respective names are downgraded to subgenera. These changes result in many new combinations, which are pointed out.
Keywords: Ptetromalidae; Anorbanus; Sedma; Monoksa; Obalana